(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2021)
This article deals with the death of the hero in the Kassena culture of West Africa (Ghana and Burkina Faso). The lack of details about the death of the illustrious individual in Kassena mythology can be interpreted in the context of a cosmology that sees the world and life as neverending processes that are always in the making and the creative actions of the ancestors as persisting. If Kassena narrations explore and embody the idea of the unfinished, this feature is to be interpreted not as incidental, but as an aesthetically congruent cultural element.